KEEFEKTIFAN STRATEGI PROJECT BASED LEARNING BERBANTUAN MODUL PADA HASIL BELAJAR KIMIA SISWA - Rose, Retha Aliefyan; Prasetya, Agung Tri (Universitas Negeri Semarang, 2014)
This study aims to determine the effectiveness of instructional strategies of project based learning module assisted on student learning outcomes on chemical material of solubility and solubility product. The population in this study was class XI PSIA student of a high school in Pemalang academic year 2011/2012. The sample in this study namely class XI PSIA 1 as experimental class with project-based learning modules assisted and class XI PSIA 3 as a control class with lecture learning with module-assisted.This study used a pretest and posttest comparison group design. Analysis results of the average differences in one right hand posttest learning outcomes at the level of 95% indicates that the average learning outcomes of experimental class greater than the control class. This result are evidenced by the estimated average test showed the average range of cognitive learning outcomes between the experimental class and the control class respectively 78.51-82.29 and 74.05-79.15. The results showed that the classical learning mastery of experimental class was 67.50% and control class was 47.50%. Affective and psychomotor learning outcomes indicated that the experimental class are better than control class. The conclusions from this study were that the implementation of project-based learning with module assisted effectively increase the student learning outcomes.Keywords: Learning Outcomes, Module, Project Based Learning